AL – NOOR NEW VARIETY OF POPCORN (Zea mays var evarta) - & et al., Mhmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Breeding program was conducted to develop new variety of popcorn (Noor) adapted to Iraqi environment during 2008 -2012 at  Al- Latifya Research Station /Agric. Res. Directorate /  Minsof Sci& Technology. The aim of this program was to develop new popcorn variety more adapted to Iraqi environment with best traits and high yield and popping expansion. Introduction and hybridization methods applied during  at the first stage among local variety AL-Safa and Syrian variety (Halab) and American variety (AMR-2). The Mass selection at later stage for five cycles respectively for new population that produced from hybridization. In fall season 2012 an experiment was conducted to compare new variety (AL- Noor) with exotic and promise genotypes including its parents by using randomized complete block design(RCBD). The rustle showed significant differences at p˃ 0.05 p for all the studied  traits except number of leaves and leaf area index and number of ears row. The new variety AL-Noor revealed lowest days a tassling and silking days (60.19  and 62.94) and highest number of ears per plant(1.63), kernels row (42.93), and number of kernels/ plant and highest poppingexpansion (987.50)ml. gm-1.